SIAP YIA: AN AIRPORT PAVEMENT INFORMATION SYSTEM FOR AIRPORT PAVEMENT DATA STORAGE - Afriyani, Suci Ryski Nur; Arinda, Nabilah Hasna; Burhanudin, Tiara; Sari, Anggi Nidya (Journal of Airport Engineering Technology (JAET), 2025)
The information system for storing pavement data at the airport remains manual and is currently focused on a single device. This study aims to design a website-based application for storing pavement data at the airport. With this application, it is expected to improve the service of the airport facilities unit. The data used in this study is pavement data from Yogyakarta International Airport. This study employs the Research and Development (R&D) method, utilizing the Waterfall model for the second stage, specifically the design stage, with planning tools that include flowcharts and use case diagrams. The design of this application also uses the App Sheet website using simple coding. Additionally, this application is compatible with various platforms, making it more flexible for use anywhere and at any time online. Of course, with this application, pavement data storage can be computerized properly, and it features a database that helps reduce the accumulation of documents and prevent the loss of documents in other files.